Systematic Study on the Relationship Between Beryllium-7 Concentration With Dynamics of Northeast Monsoon Activity - Mohd Fauzi Haris; Norita Md. Norwawi; Mohd Hafez Mohd Isa; Muhammad Rawi Mohamed Zin; Mohd Zaid Hassan Abdul Rahman; Haizum Ruzanna Sahar; Azlai Ta'at (Elsevier, 2026)
Indexed by WOS/Scopus/ERA